Optimalisasi Minat Baca Anak Melalui Penyediaan Ruang Baca Sederhana Di Kelurahan Belakang Gedung, Kecamatan Pasar Manna, Kabupaten Bengkulu Selatan - Raihan Priyatama; Mulya Bintang; Muhammad Yafi Thufail; Marshanda Ayu Anggraini; Reza Rizkie Amallia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Current technological developments have significantly changed children's patterns of leisure-time activities, as indicated by the increasing use of digital devices and the declining interest in reading. This condition is also evident in Belakang Gedung Village, Pasar Manna District, South Bengkulu Regency, where children tend to spend more time using smartphones than reading books, potentially affecting their literacy skills, critical thinking abilities, creativity, and communication skills. To address this issue, students of the Community Service Program (Kuliah Kerja Nyata/KKN) Group 112 from the University of Bengkulu implemented a community engagement program called “Ruang Tumbuh” (Growing Space), which involved the provision of a simple reading space combined with storytelling sessions, shared reading activities, interactive quizzes, and educational games aimed at fostering children's interest in reading through enjoyable and participatory approaches. The program was carried out through several stages, including community needs identification, establishment of reading facilities, implementation of literacy activities, and evaluation of participant engagement. The results demonstrated that children showed high enthusiasm throughout the program. Storytelling activities successfully attracted participants' attention to reading materials, while shared reading and engaging games encouraged more active interaction with books. In addition to increasing reading interest, the program also contributed to strengthening social interaction, enhancing children's self-confidence in expressing their opinions, and providing a positive alternative activity that may reduce dependence on digital devices. Therefore, the Ruang Tumbuh program has the potential to serve as a simple, practical, and sustainable community-based literacy model for promoting and strengthening reading culture among school-age children.